Transformation of Customer Economic Behavior in Digital World - N. V. Barinova; V. R. Barinov (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
Digitalization processes that have been energetically developing lately form a basis of considerable transformation of customer economic behavior. Digital technologies keep on perfecting by moving up to new platforms. The authors give examples of new formats of outlets, ways of payment, delivery and product marking. Changes in marketing strategies in current conditions are shown and transition to digital marketing is grounded. Advanced marketing tools, such as SEO, SMM, SMO, SEM and crowd-technology are studied. Their future development is based on research by scientists and practical workers in the field of machine training, artificial neuron networks and cognitive technologies. The article provides examples of using chat-bots, electronic assistants, mobile applications, which help customers search for goods and services. Their principle advantages are studied, which aim at rising sales and their impact on economic decision-making is analyzed. The rising role of artificial intellect and neuron networks in developing digital products is underlined. The use of artificial intellect technologies allows retail to increase sales at the expense of effective digital tools, which can improve customer loyalty to the brand. In the end the authors came to the conclusion about trends of customer economic behavior in the ear of digitalization.